Highly Efficient Synthesis of Rare Sugars from Glycerol in Endotoxin-Free ClearColi by Fermentation - Yahui Gao; Zhou Chen; Hideki Nakanishi; Zijie Li (Foods, 2023)
Rare sugars possess potential applications as low-calorie sweeteners, especially for anti-obesity and anti-diabetes. In this study, a fermentation biosystem based on the “DHAP-dependent aldolases strategy” was established for D-allulose and D-sorbose production from glycerol in endotoxin-free ClearColi BL21 (DE3). Several engineering strategies were adopted to enhance rare sugar production. Firstly, the combination of different plasmids for aldO, rhaD, and yqaB expression was optimized. Then, the artificially constructed ribosomal binding site (RBS) libraries of aldO, rhaD, and yqaB genes were assembled individually and combinatorially. In addition, a peroxidase was overexpressed to eliminate the damage or toxicity from hydrogen peroxide generated by alditol oxidase (AldO). Finally, stepwise improvements in rare sugar synthesis were elevated to 15.01 g/L with a high yield of 0.75 g/g glycerol in a 3 L fermenter. This research enables the effective production of rare sugars from raw glycerol in high yields.